Enhancement of coercivity of M-type barium hexaferrite by Ho doping. (2022) - Manglam, Murli Kumar; Shukla, Anant; Mallick, Jyotirekha; Yadav, Mukesh Kumar; Kumari, Suman; Zope, Mukesh; Kar, Manoranjan
Abstract: The present work explains the structural and magnetic properties of Ho doped barium hexaferrite. The BaFe12-x Hox O19 (x = 0.0, 0.25, and 0.50) were synthesized by the sol-gel method and annealed at 850 °C. The average crystallite size decreases with the increase in Ho concentration in barium hexaferrite. The "Law of Approach to Saturation model" is employed to determine the magnetocrystalline anisotropy constant as well as saturation magnetization. The saturation magnetization decreases and coercivity increases with the increase in Ho concentration in barium hexaferrite. The decrease of saturation magnetization with the Ho concentration could be due to the reduction of average crystallite size as well as the presence of secondary phase in the Ho doped samples. The magnetic parameters of barium hexaferrite depend on Fe-O-Fe superexchange interaction and average crystallite size which is considered to explain the magnetic properties of the Ho doped barium hexaferrite. Also, the presence of an extra phase has been considered to explain the magnetic properties of Ho doped barium hexaferrite.